2020
DOI: 10.3389/fpsyg.2020.00730
|View full text |Cite
|
Sign up to set email alerts
|

Review of EEG, ERP, and Brain Connectivity Estimators as Predictive Biomarkers of Social Anxiety Disorder

Abstract: Social anxiety disorder (SAD) is characterized by a fear of negative evaluation, negative self-belief and extreme avoidance of social situations. These recurrent symptoms are thought to maintain the severity and substantial impairment in social and cognitive thoughts. SAD is associated with a disruption in neuronal networks implicated in emotional regulation, perceptual stimulus functions, and emotion processing, suggesting a network system to delineate the electrocortical endophenotypes of SAD. This paper see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 165 publications
(268 reference statements)
0
42
0
Order By: Relevance
“…There are hundreds of studies of both EEG and fMRI modalities suggesting sensors that could become biomarkers for fear and anxiety without the subjects’ full awareness [ 37 , 38 , 39 ]. A detailed review of these modalities is beyond the scope of this manuscript, which instead focuses upon the results obtained with our novel protocol incorporating stimuli and CRs related to the two domains in the human literature of expectancy i.e., fear conditioning and anticipation of pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are hundreds of studies of both EEG and fMRI modalities suggesting sensors that could become biomarkers for fear and anxiety without the subjects’ full awareness [ 37 , 38 , 39 ]. A detailed review of these modalities is beyond the scope of this manuscript, which instead focuses upon the results obtained with our novel protocol incorporating stimuli and CRs related to the two domains in the human literature of expectancy i.e., fear conditioning and anticipation of pain.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that EEG and magneto-encephalographic spectral power, evoked responses, psychological ratings during presentation of fearful stimuli, and fear conditioning protocols may be sensors for fear and anxiety. A meta-analysis reviewing 97 studies of magneto-encephalographic activity in patients with social anxiety disorder found that the fusion of magneto-encephalographic, EEG, and fMRI results was more effective than EEG alone [ 39 ]. These studies suggest that electrophysiological activities are related to fearful stimuli and conditioned fear and may be sensors for increased trait anxiety and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, Miskovic et al [16] showed that a cognitive behavioral treatment for SAD was associated with reductions at delta-beta frequency coupling. Finally, a recent review of the most frequently studied EEG predictive biomarkers for SAD was presented by AL-Ezzi et al [17], which included frontal alpha asymmetry and delta-beta coupling as estimators. While many studies focused on SAD analysis, to the best of our knowledge, no EEG studies to date have investigated SAD detection using machine learning methods.…”
Section: Related Workmentioning
confidence: 99%
“…Electroencephalography (EEG) has emerged as a promising objective biomarker for a wide spectrum of psychiatric disorders, including depression [ 26 ], bipolar disorder [ 27 ], anxiety [ 28 ], and obsessive–compulsive disorders [ 29 ], among others. The diagnostic potential of EEG signals has already been demonstrated in adults [ 30 ], and more recently in children and adolescents [ 31 ].…”
Section: Moving Beyond the Individual To A Multi-domain Neurophenomentioning
confidence: 99%